Self-Adjustment of Gifted Students to Parental Treatment - Aldalham, Majed Saeed; khasawneh, mohmmad Ahmad (STAI Miftahul Ula Nganjuk, 2023)
There are a number of reasons that may contribute to the social difficulties of academically gifted children. This impacts the child's capacity to communicate and interact with his environment's people. The authoritarian parenting style of intellectually capable parents may have a negative effect on their children if these parents raise their children. This study focuses on the coping strategies used by extraordinarily brilliant children raised by parents with authoritarian parenting styles. This analysis employs a qualitative method, particularly a case study-based strategy. The majority of the information was gathered via interviews, observations, and document analysis. This study demonstrates that the patterns and complexities of an individual's personal adjustment may be utilized to estimate the degree to which intellectually gifted children adapt to their settings. Intellectually gifted children face problems that are not shared by other children when it comes to adjusting to their environment; yet, these obstacles may be found in each of these several kinds of adaptation. These elements may be comprehended in terms of the three major issues examined in this study. The degree to which a child with exceptional intelligence adapts to his or her surroundings may be influenced by three factors: the child's personality, the child's immediate environment, and the parents' degree of authoritarianism. Academically gifted children may have difficulty adjusting in a number of ways, including the capacity to moderate their emotions, define realistic goals for themselves, and improve on their existing skills.